Private School Leadership Management through the Mobile School Program at SMA Negeri 1 Sirah Pulau Padang - Putra, Ismail Danka; Fitria, Happy; Nurlina, Nurlina (Yayasan Sembilan Pemuda Indonesia, 2023)
This research aims to find out how the management of school principals improves the quality of education through the driving school program. This research is a field research qualitative approach method. The researcher describes the activities or behavior of the deceased, both their perceptions and opinions, as well as other aspects that are relevant to the focus of this research. The informants or key informants in this study are school supervisors, principals, teachers, and student opinions. Overall, the role of the school principal is very important in managing the Mobilize Teachers’ College program. Through good planning, effective organization, directed implementation, and careful supervision, school principals can ensure that the program runs successfully and has a positive impact on improving the quality of education in schools. Principal leadership management through the Mobilization School program at SMAN 1 Sirah Pulau Padang includes (1) planning of the Mobilizing School program; (2) organizing the resources for implementing the Mobilization School program; (3) implementation of the driving school program; and (4) supervising the implementation of the driving school program. The obstacles faced are (1) limited resources; (2) lack of support and understanding of the Mobilization School Program; (3) students are less motivated or do not participate actively in the Mobilization School Program; (4) schools need to adapt and ensure that the program remains in accordance with existing requirements; and (5) obstacles in evaluating and monitoring the Mobilization School Program. This research provides a new reference description regarding principal leadership management through the Mobilization School program.